On the validity of interpreting functional analyses of inappropriate mealtime behavior using structured criteria. Issue 4 (12th July 2022) - Guerrero, Lisa A.; Engler, Christopher W.; Hansen, Bethany A.; Piazza, Cathleen C.
Abstract : Visual inspection is the traditional method behavior analysts use to interpret functional‐analysis results. Limitations of visual inspection include lack of standardized rules, subjectivity, and inconsistent interrater reliability (Fisch, 1998). To address these limitations, researchers have developed, evaluated, and refined structured criteria to aid interpretation of functional analyses of destructive behavior (Hagopian et al., 1997; Roane et al., 2013; Saini et al., 2018). The current study applied the structured criteria Saini et al. (2018) described to functional analyses of inappropriate mealtime behavior. We assessed its predictive validity and evaluated its efficiency relative to 3 post hoc visual inspection procedures. Validity metrics were lower than those in Saini et al. however, ongoing visual inspection increased the efficiency of functional analyses by more than 30%. We discuss these findings relative to the procedural differences between functional analyses of destructive behavior and inappropriate mealtime behavior.